Ensino de física por meio de experimentos: uma aplicação da aprendizagem significativa no ensino médio - PAES, Andrey Coelho (2023)
Education is a field of activity that goes back to the beginnings of human societies. From household chores to hunting, manufacturing or even art, it all depends on a teaching and learning process. Much has been debated about the various theories about this process and how they should be implemented to achieve lasting results. In this paper, we seek to develop David Ausubel's Theory of Meaningful Learning through a pedagogical classroom experience at the Escola Salesiana do Trabalho, consisting of three subjects in two experiments: Thermal Machines and Cyclic Transformations, applied through an experiment with a steamboat and Resistors Association, applied by means of a circuit board with a shower resistor and an incandescent lamp. The results were promising, as the students' statements show that it is possible to develop an educational practice that is in fact meaningful to the target audience, the students. We hope this work can also be an incentive for more undergraduate physics students to do similar activities.